The Tsetse Fly Displays an Attenuated Immune Response to Its Secondary Symbiont, Sodalis glossinidius - Trappeniers, Katrien; Matetovici, Irina; Van Den Abbeele, Jan; De Vooght, Linda (Frontiers in Microbiology, 2019)
Sodalis glossinidius, a vertically transmitted facultative symbiont of the tsetse fly, is a bacterium in the early/intermediate state of its transition toward symbiosis, representing an important model for investigating how the insect host immune defense response is regulated to allow endosymbionts to establish a chronic infection within their hosts without being eliminated. In this study, we report on the establishment of a tsetse fly line devoid of S. glossinidius only, allowing us to experimentally investigate i) the complex immunological interactions between a single bacterial species and its host, ii) how the symbiont population is kept under control, and iii) the impact of the symbiont on the vector competence of the tsetse fly to transmit the sleeping sickness parasite. Comparative transcriptome analysis showed no difference in the expression of genes involved in innate immune processes between symbiont-harbouring (GmmSod+) and S. glossinidius-free (GmmSod-) flies. Re-exposure of (GmmSod-) flies to the endosymbiotic bacterium resulted in a moderate immune response, whereas exposure to pathogenic E. coli or to a close non-insect associated relative of S. glossinidius, i.e. S. praecaptivus, resulted in full immune activation. We also showed that S. glossinidius densities are not affected by experimental activation or suppression of the host immune system, indicating that S. glossinidius is resistant to mounted immune attacks and that the host immune system does not play a major role in controlling S. glossinidius proliferation. Finally, we demonstrate that the absence or presence of S. glossinidius in the tsetse fly does not alter its capacity to mount an immune response to pathogens nor does it affect the fly’s susceptibility towards trypanosome infection.